Integrating petrography and geochemistry data for provenance and palaeotectonic interpretation of a sedimentary deposit - Salufu, Emmanuel Omoh; Habibah Jamil; Norasiah Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Effective interpretation of provenance and tectonic settings that affected a sedimentary deposit was optimised using a geochemistry and mineralogical interdisciplinary approach. Geochemical data was integrated with petrographic data to interpret the provenance and tectonic history of some sedimentary samples selected from a sedimentary sequence exposed along Imiegba in southern Nigeria. Sixteen samples were subjected to X-ray Fluorescence (XRF) analysis to assess the essential oxide composition and eighteen were analysed for their rare earth element compositions. Ten sedimentary samples were prepared into thin sections for a mineralogical study under a petrographic microscope. The geochemical approach using the compositional plot of TiO₂, Al₂O₃, Fe₂O₃, MgO, CaO, Na₂O and K₂O of the samples on a discriminant function shows a Felsic igneous source which is confirmed by the enrichment in the light rare earth elements concentration. It also indicates intermediate and Quartzose sedimentary provenance on a passive margin and oceanic island arc. The modal composition of quartz, feldspar and rock fragments plotted on a triangular diagram indicate metamorphic, plutonic and recycled orogen provenances, with a cratonic interior, and continent transitional and basement uplift activities. The study area thus contains sedimentary deposits derived from plutonic, metamorphic, and quartzose sedimentary provenance with imprints of divergent tectonic and convergent tectonic activities.